2022
DOI: 10.1175/mwr-d-21-0201.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Explainable Machine Learning Forecasts to Discover Subseasonal Drivers of High Summer Temperatures in Western and Central Europe

Abstract: Reliable sub-seasonal forecasts of high summer temperatures would be very valuable for society. Although state-of-the-art numerical weather prediction (NWP) models have become much better in representing the relevant sources of predictability like land- and sea-surface states, the sub-seasonal potential is not fully realized. Complexities arise because drivers depend on the state of other drivers and on interactions over multiple time-scales. This study applies statistical modeling to ERA5 reanalysis data, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 97 publications
0
24
0
Order By: Relevance
“…Daily anomalies were then averaged to four-week (31-day) values for t2m and three-week (21-day) values for the other variables. In previous studies we namely found that three-week averages of SST and other variables are at least as related to four-week European t2m as four-week averages (van Straaten et al, 2022(van Straaten et al, , 2023. Both aggregations were executed as a rolling-window averaging, such that one value was recorded each day The western north Pacific (WNP) region, whose warming as part of the west Pacific warming mode was found to have strong influence on the Walker Circulation, is defined from 10 o N-30 o N 130 o E-170 o W (Funk et al, 2018).…”
Section: Datamentioning
confidence: 83%
See 2 more Smart Citations
“…Daily anomalies were then averaged to four-week (31-day) values for t2m and three-week (21-day) values for the other variables. In previous studies we namely found that three-week averages of SST and other variables are at least as related to four-week European t2m as four-week averages (van Straaten et al, 2022(van Straaten et al, , 2023. Both aggregations were executed as a rolling-window averaging, such that one value was recorded each day The western north Pacific (WNP) region, whose warming as part of the west Pacific warming mode was found to have strong influence on the Walker Circulation, is defined from 10 o N-30 o N 130 o E-170 o W (Funk et al, 2018).…”
Section: Datamentioning
confidence: 83%
“…In a previous study we used hierarchical clustering to find a west and central European region (Fig. 1B), in which the average t2m anomaly is predictable when also aggregated to the four-week or monthly time scale (van Straaten et al, 2022). Using rolling averages as described above, we thus create a four-week average response variable which we will refer to as 't2m in week 3,4,5 and 6'.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we suggest that to be useful to operational subseasonal-to-seasonal forecasters, machine learning models need to meet one (ideally all) of the following requirements: the model must have forecast skill comparable to operational numerical forecasting models; the model should help identify forecasts of opportunity at time of forecast; and the model should relate forecasts of opportunity to known dynamical climate modes. The LIM does all of these, and several other machine learning approaches currently under development may also be aiming to meet these requirements to varying degrees (e.g., Ham et al 2019, Scheuerer et al 2020, Qian et al 2020, Buchmann and DeSole 2021, Charlton-Perez et al 2021, Martin et al 2021, Mayer and Barnes 2021, Silini et al 2021, Toms et al 2021, van Straaten et al 2022.…”
Section: Looking To the Futurementioning
confidence: 99%
“…It is not, however, ideal for the study of non-linearities and interactions. Felsche and Ludwig [2021] and van Straaten et al [2022] employ more powerful regression models (neural nets and random forests) to predict droughts and heatwaves, respectively. The coefficients of those models are generally not human-interpretable.…”
Section: Introductionmentioning
confidence: 99%